2020
DOI: 10.1039/d0cs00292e
|View full text |Cite
|
Sign up to set email alerts
|

Rare-earth metal–organic frameworks: from structure to applications

Abstract: In the past 30 years, rare-earth metal–organic frameworks (MOFs) have been gaining attention owing to their diverse chemical structures, and tunable properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
211
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 319 publications
(214 citation statements)
references
References 381 publications
3
211
0
Order By: Relevance
“…[ 50–52,136 ] Moreover, the luminescence of RE ions have advantages of narrow bandwidth, long decay time, high quantum yield, large Stokes shifts, and high photostability, which is due to the shielded 4f electrons by outer electrons. [ 47,55 ] As shown in Table 1 , the luminescence of 2D RE materials is focused on RE doping types and RE hybrids, where RE can endow the 2D materials with excellent luminescence features. [ 70,80,112 ]…”
Section: Properties and Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 50–52,136 ] Moreover, the luminescence of RE ions have advantages of narrow bandwidth, long decay time, high quantum yield, large Stokes shifts, and high photostability, which is due to the shielded 4f electrons by outer electrons. [ 47,55 ] As shown in Table 1 , the luminescence of 2D RE materials is focused on RE doping types and RE hybrids, where RE can endow the 2D materials with excellent luminescence features. [ 70,80,112 ]…”
Section: Properties and Applicationsmentioning
confidence: 99%
“…[ 37,41–46 ] Briefly, RE ions have two ground‐state electron configurations including [Xe]4f n and [Xe]4f n −1 5d 1 . [ 41,47–49 ] The 4f electrons in 4f n configuration are localized core‐like and have a strong correlationship with n . [ 50–55 ] Localized 4f transitions including the f–d interconfigurational and f–f intraconfigurational transitions endow RE with atomic‐like optical transitions, which can be observed as sharp and various absorption or luminescence bands.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, the interest in lanthanide-based MOFs, LnOFs hereafter, is rising due to their versatilities in areas such as luminescence [6,7], gas adsorption [8][9][10][11], optical storage [12,13], and magnetism [14]. The problem lies on the fact that lanthanide elements have very high and variable coordination numbers, which brings us to the issue that the coordination geometries and the LnOF topologies are difficult to control [15]. Instead, once a dominant architecture is achieved and the factors affecting the structural variability are isolated [16][17][18], it allows obtaining an isostructural family of lanthanide-based materials in which a comparative analysis of a specific property may be accomplished.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] Rare-earth (RE) metals, which include scandium, yttrium and the fifteen lanthanides, have been used to synthesize a diverse library of MOFs, including many with unique structures and properties driven by the high coordination numbers and geometries of RE-metals. [17][18][19][20] Like other classes of MOFs, RE-MOFs have been reported with several different secondary building units (SBUs), including inorganic nodes that are metal ions, 21,22 chains, [23][24][25] or clusters. 5,[26][27][28][29] In 2013, Eddaoudi et al showed that the use of fluorinated modulators, such as 2-fluorobenzoic acid, favors the formation of RE-cluster nodes, instead of the ion or chain nodes that tend to preferentially form in the presence of carboxylic acid linkers.…”
Section: Introductionmentioning
confidence: 99%